Gender and race matter global perspectives on being a woman. - Takhar, Shaminder; Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research,, 2016)
The drive for gender equality is not a recent phenomenon with the UN cited as occupying a central role for legislative change globally. Gender inequality persists in most countries and although it appears that we have a long way to go, this collection contributes to a feminist scholarship that highlights a destabilising of established patterns of behaviour and gender relations. It acknowledges the multiplicity of discrimination but locates women at the centre of a dialogue and presents key interventions in gender and race matters. For the contributors, gender serves as an analytical framework and covers the experiences of women in different global settings related to education, political activism, corporeal violence, identity, sexuality, and poverty. The use of poetry and literature provides a powerful voice for women against exclusion and recognises their contribution to society. This collection is innovative in not only relating experiential evidence but also putting forward how women are able to challenge oppression through circumventing rules, roles, obligations and prejudice through a powerful agency.